Challenges in tomato cultivation and marketing: a thematic analysis - Hensman, G.H. (Journal of Agriculture and Value Addition. 4(2): 13˗25., 2022)
This paper aims to identify the challenges in the cultivation and marketing of tomatoes and the marketing mechanisms for the surplus production of tomatoes. This paper uses in-depth interviews with twenty-eight farmers and nine agricultural officials in different parts of Jaffna district. Focus group discussion was conducted to explore themes; six sub-themes were identified under two broad themes. Climatic changes, Modern technology adaptation, price fluctuation, and institutionalized policy, product diversification, and systematic marketing mechanisms were the identified sub-themes in this research study. Different strategies to overcome the climatic changes should be developed. As observed, local level adaptation and farm management system should be adapted in tomato farming system. Creation of an economic center in the region is very useful in order to avoid price fluctuations and losses faced by the farmers. Government should make policies to put up a processing center which in turn will give many employment opportunities for the youths and tomato farmers in the region.
Keywords: Challenges; Marketing mechanisms; Themes; Tomato cultivation